2015
DOI: 10.7575/aiac.alls.v.6n.3p.225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Listening Skill of ELT Textbook at Secondary School Level

Abstract: Textbook evaluation means development of textbook that is based on rigorous research. In Pakistan text books are designed on communicative language teaching which focuses on communication. Morley (1991) has asserted that listening has a critical role in communication and in language acquisition because the better the students understand, the better they will be able to speak. In our text books, listening practices (text and activities) are missing, and listening plays a secondary role as compared to speaking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The second research approach for L2 textbook evaluation concentrates on addressing a single aspect of L2 teaching and learning from a micro perspective. Examples of the aspects which particular studies have focused upon include (a) listening (Ahmed, Yaqoob & Yaqoob, 2015), (b) reading (Al-Ghazo & M. Smadi, 2013; Althewini, 2016), (c) speaking (Alkhateeb & Almujaiwel, 2018), (d) writing (Al-Qadi & Al-Qadi, 2015;Chang, 2004;Kobayakawa, 2011), (e) vocabulary (Manasrah, Al-Sobh & Al-Jabali, 2013;Mashrah, 2013), (f) culture (Allehyani, Burnapp, Wilson, 2017;Dweikat & Shbeitah, 2013), and (g) pragmatics (Vellenga, 2004). This current study also focuses on examining one single aspect of L2 teaching and learning: L2 writing.…”
Section: Evaluation Of L2 Textbooks From a Micro Perspectivementioning
confidence: 99%
“…The second research approach for L2 textbook evaluation concentrates on addressing a single aspect of L2 teaching and learning from a micro perspective. Examples of the aspects which particular studies have focused upon include (a) listening (Ahmed, Yaqoob & Yaqoob, 2015), (b) reading (Al-Ghazo & M. Smadi, 2013; Althewini, 2016), (c) speaking (Alkhateeb & Almujaiwel, 2018), (d) writing (Al-Qadi & Al-Qadi, 2015;Chang, 2004;Kobayakawa, 2011), (e) vocabulary (Manasrah, Al-Sobh & Al-Jabali, 2013;Mashrah, 2013), (f) culture (Allehyani, Burnapp, Wilson, 2017;Dweikat & Shbeitah, 2013), and (g) pragmatics (Vellenga, 2004). This current study also focuses on examining one single aspect of L2 teaching and learning: L2 writing.…”
Section: Evaluation Of L2 Textbooks From a Micro Perspectivementioning
confidence: 99%
“…Listening is the activity most often done in learning. Listening to learning in primary schools is directed to develop language skills, understanding of what is to listen to learning material, and to improve oral and written communication skills (Ahmed, Yaqoob, & Yaqoob, 2015;Bozorgian & Alamdari, 2018;Listiyaningsih, 2017). It is also found that in learning language, the proportions of people using communication time are 45% for listening, 30% for speaking, 16% for reading, and 9% for writing.…”
Section: Introductionmentioning
confidence: 99%
“…basic types of listening comprehension that differ according to listeners' goals and abilities among them are:(1) discriminative listening: the listener only distinguishes sounds without understanding (2) comprehensive listening: listener understands the message that is being communicated (3) empathic listening: listener attempts to understand the feelings and emotions of the speaker (4) participative listening: listener reacts to what he/she is listening to(Leonard (2010),Ahmed, Yacoob & Yacoob(2015) Karagoz et al ( 2017. The following section dealt with such types in some detail as follows:…”
mentioning
confidence: 99%